A Single or Short Course of Palliative Radiotherapy Increases the Risk of Pain Flare - Tanaka, Osamu; Oguchi, Masahiko (Reports of Radiotherapy and Oncology, 2016)
Objectives: To evaluate the incidence of pain flare after palliative radiation for painful osseous metastases, and whether a single or short course of radiotherapy increases the risk of pain flare using a physician-based assessment. Methods: A series of 55 consecutive patients who underwent palliative radiotherapy were included in this analysis. Their treatments were as follows: 8 Gy, single fraction (n = 5), 20 Gy, 5 fractions (n = 11), 30 Gy, 10 fractions (n = 39). Pain flare was defined as a 2-point increase in the present pain intensity (PPI) with no decrease in analgesic score or a 25% increase in the analgesic score with no decrease in PPI for at least 2 consecutive days. The assessment was performed by a radiation oncologist. Results: Using the definition of pain flare, 8 out of 34 (24%) patients experienced a pain flare with a median duration of 3 days (range: 2 to 6 days). The median onset of pain flare was the day after the start of radiotherapy (day 2; range, day 1 to 3). Two of the 5 (40%) patients and 4 of the 11 (36%) patients who received total doses of 8 Gy and 20 Gy, respectively, experienced a pain flare.In contrast, 2 of the 39 (5%) patients who received a total dose of 30 Gy experienced a pain flare. Conclusions: Pain flare is common after palliative radiotherapy for bone metastases.Single fraction or short course radiotherapy may be associated with a higher risk of pain flare.